The Effect of Murabahah, Mudharabah and Musharakah Financing on Profitability in Sharia Commercial Banks - Nora Lubis; Hilmi, Hilmi; Yusri Hazmi, (International Journal of Scientific Research and Management (IJSRM), 2024)
Financing is an important activity for Islamic banks. Islamic banks, which have a function as an intermediary institution, are obliged to carry out operational activities effectively and efficiently in order to generate maximum profits. This study aims to determine the influence of Murabahah, Mudharabah, and Musharakah Financing on profitability in Sharia Commercial Banks in Indonesia. The analysis method used is the panel data regression method with the selected model being the Fixed Effect Model. The population in this study is all Sharia Commercial Banks in Indonesia registered with the FSA for the 2019-2021 period as many as 14 Islamic banks. The determination of the number of samples was carried out using the Purposive Sampling technique and was determined as many as 9 samples of Islamic banks. The results of the t-test show that partially Murabahah Financing and Musharakah Financing do not have a significant effect on profitability, while Mudharabah Financing has a negative and significant effect on profitability. The results of Test F show that simultaneously Murabahah, Mudharabah, and Musharakah Financing has a significant effect on profitability in Sharia Commercial Banks in Indonesia registered with the Financial Services Authority for the 2019-2021 period.